Controlled Hydrolysis of Phosphate Esters: A Route to Calixarene‐Supported Rare‐Earth Clusters. Issue 13 (26th January 2023) - Hosseinzadeh, Marjan; Sanz, Sergio; van Leusen, Jan; Izarova, Natalya V.; Brechin, Euan K.; Dalgarno, Scott J.; Kögerler, Paul
Abstract: Phosphate ester bonds are widely present in nature (e. g. DNA/RNA) and can be extremely stable against hydrolysis without the help of catalysts. Previously, we showed how the combination of phosphoryl and calix[4]arene moieties in the same organic framework (LPO ) allows isolation of single lanthanide (Ln) metal ions as [Ln III (LPO )2 ](O3 SCF3 )3 . Here we report how by controlling the reaction conditions a new hydrolyzed phosphoryl‐calix[4]arene ligand (H3 LHPO ) is formed as a result of Ln III ‐mediated P–OEt bond cleavage in three out of the eight possible sites in LPO . The chelating nature of H3 LHPO traps the Ln III species in the form of [Ln III (LHPO )((EtO)2 P(O)OH)]2 dimers (Ln=La, Dy, Tb, Gd), where the Dy derivative shows slow magnetization relaxation. The strategy presented herein could be extended to access a broader library of hydrolyzed platforms (H x LHPO ; x =1–8) that may represent mimics of nuclease enzymes. Abstract : Ln‐based controlled hydrolysis in a phosphorylated‐calix[4]arene results in the cleavage of three out of the eight P−OEt bonds, forming a hydrolyzed phosphoryl‐calix[4]arene ligand (H3 LHPO ). The chelating nature of H3 LHPO traps the Ln III species in the form of [Ln III (LHPO )((EtO)2 P(O)OH)]2 (Ln=La, Dy, Tb, Gd), with the Dy derivative showing slow relaxation of the magnetization.